PENERAPAN TEKNOLOGI FERMENTASI BIO-MOL PADA PENGOLAHAN PUPUK ORGANIK ECENG GONDOK DALAM UPAYA UNTUK MENJAGA KELESTARIAN DANAU BUYAN DESA PANCASARI DAN WANAGIRI, KECAMATAN SUKASADA-BULELENG - Suranjaya, I.G.; Kartini, N.L.; Purnawan, L.R. (Buletin Udayana Mengabdi; Vol 16 No 1 (2017), 2018)
Community service activities aimed at bio-mol fermentation technology transfer in hyacinth organic fertilizer processing in an effort to preserve the Lake Buyan is part of the implementation of science and technology program for the Region (IBW) Pancasari village and sub-district Wanagiri Sukasada Buleleng. The method applied in the implementation of activities in the community empowerment program is through: (1) Coordination and participatory communication with target communities to formulate a program involving efforts to preserve the lake Buyan, from planning, operational and evaluation; (2) Extension to build public perception and understanding of the innovations or programs implemented; (3) Training and simulation of the applied Ipeks transferred to the public; (4) Assistance is meeting regularly and sustainably among companion with target communities to science and technology transferred can be carried out independently by the community. The results showed that the technology transfer activities in the processing of organic fertilizer as an effort to preserve the lake Buyan could take place as indicated by the active participation and the power of science and technology high adoption of target communities. Active participation of partners in all activities of technology transfer is fairly good, amounting to 52.8%. There is willingness of partners to produce organic fertilizers raw hyacinth independently.